Dignity through Discourse : Poverty and the Culture of Deliberation in Indian Village Democracies - Rao, Vijayendra; Sanyal, Paromita (2012)
Employing a view of culture as a communicative phenomenon involving discursive engagement, which is deeply influenced by social and economic inequalities, the authors argue that the struggle to break free of poverty is as much a cultural process as it is political and economic. In this paper, they analyze important examples of discursive spaces - public meetings in Indian village democracies (gram sabhas), where villagers make important decisions about budgetary allocations for village development and the selection of beneficiaries for anti-poverty programs. They examine 290 transcripts of gram sabhas from South India to demonstrate how they create a culture of civic/political engagement among poor people, and how definitions of poverty and beneficiary-selection criteria are understood and interrogated within them. Through this examination, they highlight the process by which gram sabhas facilitate the acquisition of crucial cultural capabilities such as discursive skills and civic agency by poor and disadvantaged groups. They illustrate how the poor and socially marginalized deploy these discursive skills in a resource-scarce and socially stratified environment in making material and non-material demands in their search for dignity. The intersection of poverty, culture, and deliberative democracy is a topic of broad relevance because it sheds light on cultural processes that can be influenced by public action in a manner that helps improve the voice and agency of the poor.